Cycling and Diabetes Prevention: Practice-Based Evidence for Public Health Action. - Jenna Panter; David Ogilvie (PLoS Medicine)
Panter and Ogilvie describe findings that link recreational and commuter cycling with reduced incidence of diabetes.